2010
DOI: 10.1111/j.1745-459x.2010.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Emulsion Compositions on Taste Thresholds and Intensity Ratings of Five Taste Compounds

Abstract: This study assessed the effects of three emulsified systems on taste thresholds and the near-threshold taste intensities of the five tastes (sweet, sour, salty, bitter and umami). Emulsions were formulated with different lipid chemical compositions. Lipid addition in an emulsified form significantly increased thresholds for sour and bitter tastes produced by citric acid and quinine hydrochloride, respectively. No significant differences were found in the threshold levels in emulsions formulated with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…We may hypothesize that these subjects perceive the bitterness difference less clearly in an oily matrix than in aqueous solution. This observation agrees with Thurgood and Martini [43] who found that the bitterness was perceived with a lower intensity in a lipid phase than in an aqueous solution.…”
Section: Nature Of the Testing Matrix: Oil Or Watersupporting
confidence: 82%
See 1 more Smart Citation
“…We may hypothesize that these subjects perceive the bitterness difference less clearly in an oily matrix than in aqueous solution. This observation agrees with Thurgood and Martini [43] who found that the bitterness was perceived with a lower intensity in a lipid phase than in an aqueous solution.…”
Section: Nature Of the Testing Matrix: Oil Or Watersupporting
confidence: 82%
“…However, any modification in the structure of the matrix (e.g. the droplet size of the emulsion [38,43]) or in the nature of the lipids [37] could also influence taste perception.…”
Section: Nature Of the Testing Matrix: Oil Or Watermentioning
confidence: 99%
“…In systems with low or intermediate viscosity, a direct dependency of sensory creaminess on the volume fraction of emulsified oil has been observed by, e.g., Akhtar, Stenzel, Murray, and Dickinson (2005), de Wijk and Prinz (2005), Dresselhuis et al (2008), and Wendin and Hall (2001), whereas droplet size appears to be of minor importance (Akhtar et al, 2005;Vingerhoeds, de Wijk, Zoet, Nixdorf, & van Aken, 2008). Interactions between emulsion composition and chemical sensations are evident from Malone, Appelqvist, and Norton (2003) who reported that emulsion concentration affects flavor release in the mouth, and from Thurgood and Martini (2010) who showed that the recognition thresholds of the five tastes significantly differ when presented in aqueous solution or in O/W emulsions, whereas Akhtar, Murray, and Dickinson (2006) did not observe any effect of incorporated flavor on the sensory perception of emulsion thickness and creaminess. The exact mechanisms which are the basis of sensations such as creaminess, fattiness or thickness are, however, still not fully understood (Terpstra et al, 2009).…”
Section: Introductionmentioning
confidence: 87%
“…This may be a physical effect, due to the different polarities of the oils affecting the distribution of the bitter molecules, or a cognitive effect due to the different affinities of different fatty acids for the CD-36 “fatty taste receptor” (135), the aroma of fatty acid oxidation products, or the bitterness of unsaturated free fatty acids (95, 136). Other workers have seen no effect of lipid type on bitter taste in emulsions (137). …”
Section: Delivery Systems To Mask Bitter Tastementioning
confidence: 96%